Co-circulation of Aedes flavivirus, Culex flavivirus, and Quang Binh virus in Shanghai, China - Yuan Fang; Yi Zhang; Zheng-Bin Zhou; Wen-Qi Shi; Shang Xia; Yuan-Yuan Li; Jia-Tong Wu; Qin Liu; Guang-Yi Lin (BMC, 2018)
Abstract Background With increases in global travel and trade, the spread of arboviruses is undoubtedly alarming. Pathogen detection in field-caught mosquitoes can provide the earliest possible warning of transmission. Insect-specific flavivirus (ISFV) has been first detected in 1991 and documented worldwide in the latest ten years. Although infection with ISFVs is apparently limited to insects, an increase in the infection rate of mosquito-borne flaviviruses may be able to induce cytopathic effects in vertebrate cells during co-infection with other human pathogens. However, little is known whether ISFVs persist in most regions of China. Methods During the mosquito activity season in 2016, a surveillance program was carried out to detect ISFVs in mosquitoes in metropolitan Shanghai, China. The presence of ISFVs was randomly tested in different species of mosquitoes using RT-PCR-based and hemi-nested PCR assays, following by the sequencing of PCR products. Sequences from positive pooled samples were compared with those deposited in GenBank. Thereafter, sequences of representative insect flaviviruses were used for further phylogenetic and molecular evolutionary analyses. Results Our investigations showed: (1) the presence of Aedes flavivirus (AEFV) in 11/161 pooled samples (nine pools in Songjiang District, one pool in Huangpu District, and one pool in Qingpu District) of Aedes albopictus, (2) the presence of Quang Binh virus (QBV) in 10/195 pooled samples (all in Chongming District) of Culex tritaeniorhynchus; and (3) the presence of Culex flavivirus (CxFV) in 9/228 pooled samples (six pools in Pudong New Area, two pools in Huangpu District, and one pool in Chongming District) of Cx. pipiens. Furthermore, phylogenetic analyses of the gene sequences of envelope proteins indicated that Shanghai CxFV strains belonged to the Asia/USA genotype. The overall maximum likelihood estimation values (and 95% confidence interval) for CxFV, QBV, and AEFV in mosquitoes collected in Shanghai in 2016 were 1.34 (0.66-2.45), 1.65 (0.87-2.85), and 1.51 (0.77-2.70) per 1000, respectively. Conclusions This study reveals the presence and the geographical distribution of ISFVs, and determines the genetic variation and the infection rate of ISFVs in Shanghai, China. At least, three insect flaviviruses including ISFVs, AEFV, CxFV, and QBV, co-circulate in this area. To our knowledge, this is the first report of AEFV in China.